Arrangement of Slum Areas on the Banks of the Siwatu River in Tegal City: Penataan Kawasan Permukiman Kumuh Bantaran Sungai Siwatu Kelurahan Tegalsari Kota Tegal - Maulida, Tyas Ayu; Niravita, Aprila (Faculty of Law, Universitas Negeri Semarang, 2024)
This research analyzes the government's efforts to overcome slum settlements on the banks of the Siwatu River, Tegalsari Village, Tegal City. The aim is to find out the efforts and stages of activities carried out by the government in overcoming the problem of slum settlements. The research method used is qualitative with an empirical juridical approach. Data was collected through interviews, observation, literature study and documentation. The research results show that the government's efforts to overcome slum settlements on the banks of the Siwatu River include restoration, rejuvenation, maintenance and prevention stages, without carrying out the resettlement stage. In conclusion, the efforts made are appropriate as can be seen from the area of ​​slum settlements which decreases every year, but the government must tighten the prevention measures to prevent the formation of new slum areas.